Recommendations for the Use of ICT in Elderly Populations with Affective Disorders - Gros, Auriane; Bensamoun, David; Manera, Valeria; Fabre, Roxane; Zacconi-Cauvin, Anne-Marie; Thummler, Susanne; Benoit, Michel; Robert, Philippe; David, Renaud (Frontiers in Aging Neuroscience, 2016)
Objective: Affective disorders are frequently encountered among elderly populations, and the use of Information and Communication Technologies (ICT) could provide an added value for their recognition and assessment in addition to current clinical methods. The diversity and lack of consensus in the emerging field of ICTs is however a strong limitation for their global use in daily practice. The aim of the present article is to provide recommendations for the use of ICTs for the assessment and management of affective disorders among elderly populations with or without dementia. Methods: A Delphi panel was organized to gather recommendations from experts in the domain. A set of initial general questions for the use of ICT in affective disorders was used to guide the discussion of the expert panel and to analyze the Strengths, Weaknesses, Opportunities, and Threats (SWOT) of employing ICT in elderly populations with affective disorders. Based on the results collected from this first round, a web survey was sent to local general practitioners (GPs) and to all interns in psychiatry in France. Results: The results of the first round revealed that ICT may offer very useful tools for practitioners involved in the diagnosis and management of affective disorders. However, the results of the web survey showed the interest to better explain to current and coming practitioners the utility of ICT especially for AD patients.